The position of the Atabic of Damascus on the Crusader invasion of the Levant 497-549 / 1103-1154 AD - Durieed Nory (آداب الرافدين, 1979)
Prior to the Crusader invasion, the Levant region was experiencing a state of complexity surrounding its political, economic and religious situation, as it was governed by different powers, and internal disputes often characterize that difference, at a time when the Crusader forces seized appropriate opportunities to anticipate the opponent, and then establish it as a king over The ruins of that architecture. The Abbasid Caliphate in Baghdad wanted to preserve the Levant as part of its possessions, and the Fatimids in Egypt saw the Levant as a natural extension of Egypt and a military base with which they could secure Egypt's eastern borders against the Romans and the Abbasids and make it a base for the propagation of their doctrine. As for the Crusaders, their eyes turned to the Levant to win various spoils, including that they found in Palestine a high center for religious and political gains. The Levant region - including Antakya - was the important trade route linking European countries with the eastern world. In addition to the fact that, for the invaders, Damascus was a country of wealth and beauty, which brought many of the poor and feudal lords many rewards. On the other hand, the Levant region was inhabited by several distinct forces, and they often fought each other, including: the followers of the Fatimids, the local Arab tribes, the princes, the military leaders of the Seljuks and the Turks, in addition to the general body of the population. The Crusaders took advantage of the general conditions of the Levant and advanced to occupy some of its cities, after they used against the Muslims all the colors of lying to ignite the feeling of Christianity against them, in order to spend in their war of soul and money, and they reached it on August 15, 489 AD / 1096 AD. And other local forces.